The test-retest reliability and agreement between a fixed frame and belt-stabilised handheld dynamometer for isometric hip flexion and extension peak force measurement in recreational cyclists - Dion D’Mello; Benn Digweed; Tom Hughes (PLoS ONE, 2026)
Introduction Cycling performance is influenced by hip flexor and extensor muscle strength. While belt stabilised handheld dynamometers (B-HHD) are valid for measuring isometric hip muscle strength, fixed frame dynamometers are becoming popular, offering potentially better stability and reliability. However, the reliability of both devices has not been examined in cyclists. This study evaluated the test-retest reliability and agreement between a B-HHD (MicroFET2, Hoggan Scientific) and a fixed-frame dynamometer (ForceFrame (FF) Max, Vald Performance) for hip flexion and extension peak force measurement in cyclists. Methods A test-retest design was used. Twenty-five recreational cyclists (age ± SD: 36.64 (±12.34) years; 22 males) were tested twice, approximately 72 hours apart. Three unilateral maximal voluntary isometric contractions (MVIC) of the hip flexors and extensors of each limb were performed, using the B-HHD and FF in a random order. Within and between session reliability was determined using intraclass correlation coefficients (ICCs) 3.1 & 3.k. Standard error of measurements (SEM) and minimal detectable changes (MDC) were calculated. Agreement was assessed using 95% limits of agreement (LOA). Results For hip flexion, within and between session reliability was good to excellent, and SEMs were similar (B-HHD ICCs = 0.77–0.93, SEMs = 14.25–22.71N (7.19–10.38%); FF ICCs = 0.77–0.95, SEMs = 7.80N–18.98N (3.47%−8.54%)). FF MDCs were lower within-session (21.61–39.48N (9.60–17.97%)) than B-HHD MDCs (39.50–62.95N (19.94–28.78%)), but similar between-sessions (FF MDCs = 41.25–52.61N (19.42–23.66%); B-HHD MDCs = 41.21N–48.95N (18.53–23.77%)). For hip extension, both devices demonstrated good to excellent reliability and SEMs were similar (B-HHD ICCs = 0.90–0.95, SEMs = 15.77–21.53N (7.38–9.96%); FF ICCs = 0.85–0.95, SEMs = 19.21–29.05N (7.82–11.78%) within and between sessions). All LOA exceeded a 20N acceptability threshold. Conclusion Both devices are reliable in recreational cyclists, but large MDCs suggest that caution is needed when interpreting repeated measurements. Due to poor agreement, the devices are not interchangeable so should be considered device specific. In practice, our preliminary results suggest FF data cannot be compared with B-HHD data and vice versa, so the same device should be used for repeated measurements in this population.